Effects of Resveratrol on Tight Junction Proteins and the Notch1 Pathway in an HT-29 Cell Model of Inflammation Induced by Lipopolysaccharide - Luo, Yihua; Yu, Xueyan; Zhao, Peizhuang; Huang, Jun; Huang, Xue (Inflammation, 2022)
Ulcerative colitis (UC) is closely associated with disruption of intestinal epithelial tight junction proteins. A variety of studies have confirmed that resveratrol (RSV), a natural polyphenolic compound, has a potential anti-inflammatory effect and can regulate the expression of tight junction proteins. However, the mechanism by which RSV regulates the expression of tight junction proteins in the intestinal epithelium remains unclear. Therefore, we investigated the potential effect of RSV on tight junction proteins in an HT-29 cell model of inflammation induced by lipopolysaccharide (LPS) and explored its mechanism of action. First, the downregulated expression of the tight junction proteins occludin, ZO-1, and claudin-1 in the HT-29 cell model of inflammation induced by LPS was reversed by incubation with RSV, accompanied by a decrease in the expression of tumor necrosis factor α-converting enzyme (TACE). Additionally, the Notch1 pathway was attenuated and the expression of the inflammatory factors IL-6 and TNF-α was decreased by treatment with RSV. Second, after Jagged-1 was used in combination with RSV to reactivate the Notch1 pathway, the protective effects of RSV against the LPS-induced reductions in the expression of the tight junction proteins occludin, ZO-1, and claudin-1 and the decreases in the levels of the inflammatory factors IL-6 and TNF-α were abolished. These results suggest that RSV might regulate the expression of tight junction proteins by attenuating the Notch1 pathway.